GEOPOLITIK KEPEMIMPINAN GLOBAL DAN KOMPETISI SUMBER DAYA: PERSPEKTIF INDO- PASIFIK DAN PETA ULANG DOKTRIN PERTAHANAN RI - M. Effendi; Rudi Hartono, Tarsisius Susilo, Setiawan Arismunandar, Edi Wahyudi (JOURNAL OF LAW AND NATION, 2026)
The contest for global leadership is increasingly centered in the Indo-Pacific, where major powers the United States, China, and Russia are vying for strategic resources. This rivalry spans multiple domains (energy, critical minerals, technology, land, and information) and is reshaping the region’s security architecture. This article examines how resource competition (for example, disputes over oil in the South China Sea, the 5G and semiconductor race, and struggles for supply routes) is impacting Indo- Pacific geopolitics and influencing Indonesia’s security environment. It underlines the urgency for Indonesia to respond by recalibrating its national defense doctrine. Grounded in the Asta Cita 2045 vision, Indonesia must formulate an adaptive defense doctrine that strengthens maritime security, multi-domain capabilities (cyber and space), and defense diplomacy all while upholding its independent and active foreign policy. Using an interdisciplinary approach, this study identifies patterns of resource rivalry among great powers, assesses the threats and opportunities for Indonesia, evaluates gaps in Indonesia’s current defense doctrine, and proposes a new “Indo-Pacific” defense doctrine framework aligned with the Indonesia Gold 2045 agenda. The analysis recommends a proactive and comprehensive Indonesian defense doctrine to safeguard sovereignty and national resources amid global rivalry, enabling Indonesia to contribute constructively to regional stability toward 2045.